2012
DOI: 10.1037/a0027664
|View full text |Cite
|
Sign up to set email alerts
|

Postdeployment Battlemind training for the U.K. armed forces: A cluster randomized controlled trial.

Abstract: Objective: Combat exposure can increase the risk of subsequent psychological ill-health in armed forces (AF) personnel. A U.S. postdeployment psycho-educational intervention, Battlemind, showed a beneficial effect on mental health in U.S. military personnel exposed to high combat levels.We evaluated the effectiveness of an anglicized version of postdeployment Battlemind. Method:Battlemind was adapted for the United Kingdom. The main amendments were to sections about carrying weapons, driving, and alcohol misus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 37 publications
(59 reference statements)
2
62
0
Order By: Relevance
“…A limited body of evidence examining psychoeducation approaches does not currently support the efficacy of these interventions in preventing PTSD . Battlemind, an intervention for military personnel exposed to combat trauma which was adapted from PD, found preliminary support from a study randomized at the platoon level but did not show an effect in another study (Adler et al, 2011;Mulligan et al, 2012). A study using an informational video designed for sexual assault survivors found reduced PTSD symptoms at 6 weeks only for women with a prior history of sexual assault, with the effect disappearing at 6 months (Resnick et al, 2007).…”
Section: Psychosocial Approachesmentioning
confidence: 93%
“…A limited body of evidence examining psychoeducation approaches does not currently support the efficacy of these interventions in preventing PTSD . Battlemind, an intervention for military personnel exposed to combat trauma which was adapted from PD, found preliminary support from a study randomized at the platoon level but did not show an effect in another study (Adler et al, 2011;Mulligan et al, 2012). A study using an informational video designed for sexual assault survivors found reduced PTSD symptoms at 6 weeks only for women with a prior history of sexual assault, with the effect disappearing at 6 months (Resnick et al, 2007).…”
Section: Psychosocial Approachesmentioning
confidence: 93%
“…It turned out that the range of mental health interventions implemented in different western armed forces is to a great extent similar (Vermetten et al 2014). This seems to be due to the fact that most mental health interventions draw on psychiatrist and psychologist models and the fact that the policies of different armies have influenced one another (see e.g., Boermans et al 2012;Mulligan et al 2012). As such, we can say that many contemporary western armed forces have developed what might be named a similar 'PTSD-infrastructure,' by which we refer to the structure of military interventions oriented toward PTSD.…”
Section: Literature Analysismentioning
confidence: 95%
“…The current intervention programs in western armed forces such as the US, UK, and Dutch armed forces draw on mainstream scientific understandings of PTSD (Mulligan et al 2012;Adler et al 2013;Steenkamp, Nash, and Litz 2013). The dominant PTSD-concept defines post-traumatic illness as a set of psychiatric symptoms that develop due to exposure to threatened or actual violence (American Psychiatric Association 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Boulos and Zamorski 54 Engelhard et al 60 Fear et al 10 (Afghanistan) Hoge et al 5 (Afghanistan) Hoge et al 22 (Afghanstan) Jones et al 64 Lapierre et al 67 (Afghanistan) Mulligan et al 72 Shen et al 79 have suggested this may be due to role distribution, but this finding is not universal. 13,[30][31][32][33][34] Recent research has also suggested that men and women can experience different stressors on deployment.…”
Section: Afghanistanmentioning
confidence: 96%